EVALUATING THE EFFECT OF SALINITY, PRESSURE AND TEMPERATURE ON CO2-WATER-ROCK REACTION IN BASALT - KASHIM, MUHAMMAD ZUHAILI (2021)
Mineral carbonation in geological media has been identified as the safest and permanent form of carbon dioxide (CO2) sequestration to mitigate the greenhouse issues